Kohesi Sosial dan Partisipasi Masyarakat dalam Pengembangan Desa Wisata Sejarah: Perspektif Sosiologi Pembangunan di Desa Bangsri, Kecamatan Jepon, Kabupaten Blora - Windy Ayu Septia; Agus Nurhadi (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the role of the community in the development of Bangsri Tourism Village, which is an example of a successful community-based tourism village. The study focuses on two main aspects, namely the process of establishing a tourism village involving forms and stages of participation, as well as the level and impact of community involvement in the development of the tourism village. The research method used is qualitative with a descriptive approach. Data was collected through observation, in-depth interviews, and documentation, with key informants selected based on their knowledge and experience related to the phenomenon being studied. The results of the study show that community leaders play a central role in mobilizing community involvement. Collaboration, openness, and coordination among parties are important factors in the success of the development of Bangsri Tourism Village. The community is actively involved in the decision-making process, the provision of resources, and the contribution of skills and ideas, reflecting the level of partnership participation according to Arnstein's ladder of participation theory. The impact of this participation is evident in social aspects, such as increased social cohesion and a sense of belonging to the village, as well as economic aspects, such as increased community income. This study emphasizes the importance of community involvement as the core of sustainable tourism development.